Unlocking academic success: How growth mindset interventions enhance student performance through self-belief and effort regulation - Ying Ba; Wei Ming; Hanjie Zhang (Acta Psychologica)
This research investigates how growth mindset interventions, including internal and external subscales, affect academic performance in rural Chinese schools. The research focuses on two mediators: self-belief and effort regulation. The study design adopts a purposive sample method to avoid bias, with data collected at two lags from 324 students. The data was analyzed using Structural Equation Modeling (SEM) with Smart PLS. The findings indicate that internal and external growth mindsets have no direct impact on academic performance. However, their mediating effects via self-belief and effort regulation have a considerable and positive influence on academic performance. This demonstrates that the suggested mechanism makes a significant contribution. The results show that a growth mindset promotes self-efficacy and effort-regulation, which improves students' academic performance, especially in rural schooling. Theoretically, this study enhances growth mindset theory by defining mediating mechanisms in a distinct rural environment, extending established models to unexplored educational contexts. In practice, our findings give practical insights for educators and policymakers, promoting culturally relevant interventions such as teacher training and targeted student workshops to enhance academic performance via self-regulatory behaviors.